2009
DOI: 10.1155/2010/375878
|View full text |Cite
|
Sign up to set email alerts
|

Should My Patient with Inflammatory Bowel Disease on Immunosuppressive Therapy be Vaccinated against Influenza Virus?

Abstract: Crohn's disease and ulcerative colitis are variants of inflammatory bowel disease (IBD) for which immunosuppressive therapy is often required. Immunosuppressed patients are at increased risk for infections, including vaccine-preventable diseases such as influenza. Although several guidelines recommend routine influenza immunization for such patients, recent literature suggests that this patient population may be inadequately immunized. Current research suggests that inactivated influenza vaccines are effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In contrast, patients with IBD did not suffer from an increased frequency of IBD flares after SARS-CoV-2 vaccination. Recent studies also proved the safety of other vaccines, such as the influenza vaccine, in patients with IBD [13,14]. A recent umbrella review of meta-analyses showed that vaccinations are not associated with an increased risk of IBD [15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, patients with IBD did not suffer from an increased frequency of IBD flares after SARS-CoV-2 vaccination. Recent studies also proved the safety of other vaccines, such as the influenza vaccine, in patients with IBD [13,14]. A recent umbrella review of meta-analyses showed that vaccinations are not associated with an increased risk of IBD [15].…”
Section: Discussionmentioning
confidence: 99%
“…Because immunomodulators are used to treat IBD patients, these patients are susceptible to infection, with a high rate of morbidity and mortality [92,93]. Therefore, this group of patients should be immunized prophylactically against these infections [94], preferably upon initial presentation and once the start of immunosuppressive agents is planned [95]. Given the increased risk of vaccine-related infections, live vaccines should be avoided in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of influenza vaccines in patients with immune-mediated diseases is similar to the general population. Studies in these patients show no relationship between clinical activity and vaccination (18,39). Immune response to vaccination may be diminished in patients with IBD on immunosuppressants or immunomodulators: Mamula et al analyzed response rates in children with IBD and observed seroconversion in 33 to 85 % of vaccine recipients, with response percentage being lower in those on combined therapy with immunomodulators and infliximab (40).…”
Section: Influenza Vaccinementioning
confidence: 99%